Desarrollo de la personalidad en los estudiantes - Carrasco Carrasco, Christian Javier (2017)
The present project is based on the need that individuals present, which is a lack of good behavior and the formation of their personality in the social circle that interact, with a vision to improve the quality of education and society against to the problematic on the development of the personality in the students and their behavior in the classroom and outside , it was fundamental to carry out a diagnostic investigation in a global way, on the development of the personality, through the application of the strategies of scientific research using stories such as ; direct observation, the same that allowed them to identify the variables of the object of study, transcendental activities that solve their own reality, raising the various variables that help to balance the components they intend to establish for improve student´s learning; In this case, improve the behavior of individuals in the different areas where they are deployed. The purpose is to improve the student's behavior in and out of development, for the same reason will be drawn various alternatives as motivations or educational talks, among others that allow the development of personality and thus achieve the appropriate level of behavior,